Ikigai: the evolving Japanese secret to a long and happy life - Mohd Nasir, Hazira; Musa, Aini Hayati; Mohd Zaid, Noor Azila; Mohd Nasir, Nadia (Universiti Teknologi MARA Cawangan Negeri Sembilan Kampus Rembau, 2025)
In Okinawa, a region known for its high number of centenarians, researchers often link longevity not only to diet and exercise but also to a strong sense of purpose called Ikigai. Ikigai represents the reason for living and combines purpose, community, and mindfulness, which contribute to greater health and happiness. Although it is commonly illustrated in the West as a Venn diagram connecting passion, skills, societal needs, and income, this simplified model does not fully capture the deeper cultural meaning of the concept.